Hippocampal neurons code individual episodic memories in humans - Kolibius, Luca D.; Roux, Frederic; Parish, George; Ter Wal, Marije; Van Der Plas, Mircea; Chelvarajah, Ramesh; Sawlani, Vijay; Rollings, David T.; Lang, Johannes; Gollwitzer, Stephanie; Walther, Katrin; Hopfengärtner, Rüdiger; et al. (Nature Human Behaviour, 2023)
The hippocampus is an essential hub for episodic memory processing. However, how human hippocampal single neurons code multi-element associations remains unknown. In particular, it is debated whether each hippocampal neuron represents an invariant element within an episode or whether single neurons bind together all the elements of a discrete episodic memory. Here we provide evidence for the latter hypothesis. Using single-neuron recordings from a total of 30 participants, we show that individual neurons, which we term episode-specific neurons, code discrete episodic memories using either a rate code or a temporal firing code. These neurons were observed exclusively in the hippocampus. Importantly, these episode-specific neurons do not reflect the coding of a particular element in the episode (that is, concept or time). Instead, they code for the conjunction of the different elements that make up the episode.
CRIS-Team Scopus Importer:2023-10-20